“Tem hora pra tudo”: The reframing adverstising of VIVO in “Conexão” to the isolation market - Vieira, Tacicleide Dantas; Camargo, Gabriella Cristina Vaz [UNESP] (Biblioteca Central da UNB, 2022)
The pandemic of the new coronavirus has (re)configured several projects of saying, in the varied spheres of discursive communication. In advertising, the responses elicited were quick. An example is the utterance “Conexão” (2020), which belongs to VIVO's campaign “Tem hora pra tudo” (2018/2020), which is the corpus of the analysis. In order to interpret this advertising film in its concrete and living enunciative unit, understanding its meanings/values/positions, we resort to Bakhtinian theoretical-methodological propositions, above all to the notions of chronotope, ideological sign and utterance. Through the analysis, we found that the brand's enunciative choices resignify its campaign for the “connection” (virtual) as social value and merchandise.
“Tem hora pra tudo: La (re)significación publicitaria de la VIVO en Conexão al mercado del aislamiento
“TEM HORA PRA TUDO”: A (RES)SIGNIFICAÇÃO PUBLICITÁRIA DA VIVO EM “CONEXÃO” AO MERCADO DO ISOLAMENTO
Keywords: advertising film; ideological sign; pandemic chronotope; uterrance; VIVO